Design and optimization of a novel chitosan coating system for acupoint catgut embedding materials. Issue 8 (April 2019) - Fu, Shaoju; Zhang, Peihua
Chitosan coating on acupoint catgut embedding therapy (ACET) is a critical issue in improving the comprehensive performances of embedding materials. However, the existing coating technologies have struggled to keep pace with both the academic study and industrial production. This work proposed a novel chitosan coating system consisted of pretreatment, spray-coating and rolling and drying parts. To evaluate the feasibility of this system, four types of monofilaments, namely polypropylene (PP), polylactic acid (PLA), polydioxanone (PDO) and polyglycolide acid (PGA), were adopted and their properties, such as swelling, compression and hydrophilicity, were also measured. Meanwhile, several numerical calculations and analyses were conducted to select and optimize the testing variables. The results showed that the coating concentration of 3% (v/v) was selected as the most suitable parameter; samples with the rotational speed of 2.12 m/min were demonstrated to have regular swelling behavior: PP (weight changes = 3.876 ± 0.312 g/cm, diameter changes = 1.354 ± 0.153 mm) < PLA (weight changes = 5.246 ± 0.215 g/cm, diameter changes = 3.251 ± 0.136 mm)< PDO (weight changes = 7.315 ± 0.315 g/cm, diameter changes = 5.426 ± 0.128 mm) < PGA (weight changes =9.845 ± 0.251 g/cm, diameter changes = 7.652 ± 0.248 mm); testing properties of samples were closer to the expected results regarding the decrease of contact force, so 0.1 cN was selected as the optimum parameter. In summary, the coating system was successfully developed and has a potential application for fabricating ideal embedding materials to satisfy clinical needs.